(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2021)
This paper explores the implementation of narrative learning in first-year architectural design studios and how it can amplify the making, communicating and reflecting aspects of the study. In particular, this paper examines the estrangement technique, which enables an objective view of a story and its telling. The technique allows the students to detach an existing narrative from its context to be analysed, and then recontextualise it. We focus on the main studio project for the first-semester architecture and interior architecture students in Universitas Indonesia as the context of this study. This paper analyses their process, final outputs, and feedback to see the lesson learned from their perspective. The study suggests that learning narrative framework in architectural design studio supports the students to think systematically. In the end, estrangement technique provides the students with a way to retain some aspects of a narrative while playing with others, producing a fresh view on telling stories through enhancing their ambiguity and interaction between design author and their audience.